2022
DOI: 10.1002/ajmg.a.62944
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of genetic and phenotypic heterogeneity in 37 Turkish patients with Kabuki and Kabuki‐like phenotype

Abstract: Kabuki syndrome (KS) is a rare disorder characterized by distinct face, persistent fingertip pads, and intellectual disability (ID) caused by mutation in KMT2D (56%–76%) or KDM6A (5%–8%). Thirty‐seven children aged 1–16 years who followed for median of 6.8 years were included in this study, which aimed to investigate the genetic and clinical characteristics of KS patients. KMT2D and KDM6A were evaluated by sequencing and multiplex‐ligation‐dependent probe amplification in 32 patients. Twenty‐one pathogenic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Mutations in the KDM6A gene account for approximately 5% of patients. Kabuki syndrome is very rare in Turkiye, and in a recent study by Usluer et al, 8 a KMT2D mutation was found in 21 of 32 patients (65%) who were diagnosed with Kabuki syndrome. 2,3 Our patient's typical facial appearance, ophthalmologic findings, existing renal anomaly, and KMT2D gene mutation found in genetic analysis supported the diagnosis of Kabuki syndrome.…”
Section: Discussionmentioning
confidence: 88%
“…Mutations in the KDM6A gene account for approximately 5% of patients. Kabuki syndrome is very rare in Turkiye, and in a recent study by Usluer et al, 8 a KMT2D mutation was found in 21 of 32 patients (65%) who were diagnosed with Kabuki syndrome. 2,3 Our patient's typical facial appearance, ophthalmologic findings, existing renal anomaly, and KMT2D gene mutation found in genetic analysis supported the diagnosis of Kabuki syndrome.…”
Section: Discussionmentioning
confidence: 88%
“…2022 ). A distinctive facial characteristic of patients with KS was the eversion of the lateral third of the lower eyelids, as well as long palpebral fissures, a flattened nasal tip, and enormous ears ( Usluer et al . 2022 ).…”
Section: Introductionmentioning
confidence: 99%